The Combination Effect of the Active Fractions of Ficus mucuso Welw. Ex Ficalho and Standard Antibiotics against Selected Uropathogens (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Urinary tract infections (UTIs) are a global health challenge, causing high mortality rates annually. With rising antimicrobial resistance, the search for effective alternatives has intensified. Medicinal plants serve as substitutes. Ficus mucuso Welw. Ex Fichalo has been purportedly used in ethnomedicine for the treatment of UTIs.Objective: To evaluate the antibacterial effects of Ficus mucuso extract and fractions on UTI isolates and assess synergy with first-line antibiotics.Methods: Pulverized leaves of Ficus mucuso were extracted with methanol by cold maceration. The crude extract was partitioned into n- hexane, ethyl acetate and methanol. Qualitative and quantitative phytochemical screening was carried out. Antioxidant activity of the plant was assessed. Antibiogram of clinical uropathogenic isolates and standard strains was determined using disc-diffusion method. The antimicrobial efficacy of plant extract was tested using agar-well diffusion. Bioassay-guided fractionation of the active fractions was by vacuum liquid chromatography. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values were determined via microbroth dilution assay. Combination antimicrobial testing with ciprofloxacin and amoxicillin-clavulanate was performed using checkerboard assay. Brine-shrimp assay was used to assess cytotoxicity of the plant.Results: The secondary metabolites detected; flavonoids (98.41mg/g), phenols (79.17mg/g) and tannins (27.26mg/g) were more abundant in the ethyl acetate fraction.  The plant had appreciable antioxidant activity. Plant extracts and fractions had appreciable inhibitory activities against MDR bacteria with MIC and MBC ranges of 1.5625 to 12.5mg/mL 3.125 and 25mg/mL respectively. Combination testing indicated a synergistic effect with ciprofloxacin. Cytotoxicity assay yielded LC50 value of 31.30 µg/mL.Conclusion: Leaf extracts of Ficus mucuso have antimicrobial potentials which demonstrated enhanced synergistic activity against UTI organisms when combined with standard chemotherapeutics